The Bases, U.S. Intervention and the Aquino Regime - Boone Schirmer, Daniel (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Today the Philippine bases are essential to U.S. military intervention in the Mideast, and there is a growing opposition to the bases in the Philippine Congress and in the public at large. It was just such a conjunction of circumstances--U.S. military intervention in Vietnam supplied by Philippine bases and a growing Philippine opposition to the bases--that was an element in the U.S. support for martial law in 1972. Such maybe again the case today, with or without Aquino.